STRESS AND PRESSURE IN STUDENTS BEFORE EXAMS - Trigulova T. A; Yunusova F. B (TADQIQOTLAR, 2026)
Abstract Stress is an unavoidable aspect of human life that significantly impacts students, particularly before exams. Academic pressure, coupled with high expectations from parents, teachers, peers, and self-imposed standards, can lead to anxiety, sleeplessness, and emotional strain. This study explores the multifaceted nature of pre-exam stress, examining its causes, manifestations, and consequences on students’ physical, mental, and social well-being. Factors such as workload, time management, health, and emotional resilience are considered, alongside the effects on concentration, sleep patterns, and interpersonal relationships. Understanding these stressors is crucial for developing effective coping strategies and support mechanisms. The study highlights the importance of interventions from academic institutions, families, and students themselves to reduce stress, enhance mental health, and improve academic outcomes.